Differential regulation of C5a receptor 1 in innate immune cells during the allergic asthma effector phase - Ender, Fanny (PLoS One, 2017)
C5a drives airway constriction and inflammation during the effector phase of allergic asthma, mainly through the activation of C5a receptor 1 (C5aR1). Yet, C5aR1 expression on myeloid and lymphoid cells during the allergic effector phase is ill-defined. Recently, we generated and characterized a floxed green fluorescent protein (GFP)-C5aR1 knock-in mouse. Here, we used this reporter strain to monitor C5aR1 expression in airway, pulmonary and lymph node cells during the effector phase of OVA-driven allergic asthma. C5aR1 reporter and wildtype mice developed a similar allergic phenotype with comparable airway resistance, mucus production, eosinophilic/neutrophilic airway inflammation and Th2/Th17 cytokine production. During the allergic effector phase, C5aR1 expression increased in lung tissue eosinophils but decreased in airway and pulmonary macrophages as well as in pulmonary CD11b(+) conventional dendritic cells (cDCs) and monocyte-derived DCs (moDCs). Surprisingly, expression in neutrophils was not affected. Of note, moDCs but not CD11b(+) cDCs from mediastinal lymph nodes (mLN) expressed less C5aR1 than DCs residing in the lung after OVA challenge. Finally, neither CD103(+) cDCs nor cells of the lymphoid lineage such as Th2 or Th17-differentiated CD4(+) T cells, B cells or type 2 innate lymphoid cells (ILC2) expressed C5aR1 under allergic conditions. Our findings demonstrate a complex regulation pattern of C5aR1 in the airways, lung tissue and mLN of mice, suggesting that the C5a/C5aR1 axis controls airway constriction and inflammation through activation of myeloid cells in all three compartments in an experimental model of allergic asthma.